The road out : a teacher's odyssey in poor America - Hicks, Deborah (Simpson, imprint in humanities., 2013)
Can one teacher truly make a difference in her students' lives when everything is working against them? Can a love for literature and learning save the most vulnerable of youth from a life of poverty? The Road Out is a gripping account of one teacher's journey of hope and discovery with her students-girls growing up poor in a neighborhood that was once home to white Appalachian workers, and is now a ghetto. Deborah Hicks, set out to give one group of girls something she never had: a first-rate education, and a chance to live their dreams. A contemporary tragedy is brought to life as she.